Repair of the Injured Spinal Cord by Schwann Cell Transplantation - Fu, Haitao; Hu, Die; Chen, Jinli; Wang, Qizun; Zhang, Yingze; Qi, Chao; Yu, Tengbo (Frontiers in Neuroscience, 2022)
Spinal cord injury (SCI) can result in sensorimotor impairments or disability. Studies of the cellular response to SCI have increased our understanding of nerve regenerative failure following spinal cord trauma. Biological, engineering and rehabilitation strategies for repairing the injured spinal cord have shown impressive results in SCI models of both rodents and nonhuman primates. Cell transplantation, in particular, is becoming a highly promising approach due to the cells’ capacity to provide multiple benefits at the molecular, cellular, and circuit levels. While various cell types have been investigated, we focus on the use of Schwann cells (SCs) to promote SCI repair in this review. Transplantation of SCs promotes functional recovery in animal models and is safe for use in humans with subacute SCI. The rationales for the therapeutic use of SCs for SCI include enhancement of axon regeneration, remyelination of newborn or sparing axons, and maintenance of the survival of damaged tissue. However, little is known about the molecular mechanisms by which transplanted SCs exert a reparative effect on SCI. Moreover, SC-based therapeutic strategies face considerable challenges in preclinical studies. These issues must be clarified to make SC transplantation a feasible clinical option. In this review, we summarize the recent advances in SC transplantation for SCI, and highlight proposed mechanisms and challenges of SC-mediated therapy. The sparse information available on SC clinical application in patients with SCI is also discussed.